(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the image of Aga-yi Buzurg in Hafiz Basir’s Sufi treatise Mazhar al-Aja’ib as one of the most significant female religious figures in the hagiographical literature of sixteenth-century Maverannahr. Based on textual and historical-religious analysis, the study explores the mechanisms through which her spiritual authority was constructed, the specific features of the representation of female sainthood, and the ways in which her status as a spiritual mentor was legitimized within the Sufi milieu. The analysis demonstrates that the author consistently endows Aga-yi Buzurg with the functions of a spiritual guide, teacher, and bearer of sacred knowledge by employing motifs characteristic of Sufi hagiography, including miraculous powers (karāmāt), insight into hidden realities, spiritual guidance, and posthumous veneration. Particular attention is devoted to the gender dimension of the narrative, in which models of religious authority traditionally associated with male figures are transferred to a female protagonist. The study concludes that the image of Aga-yi Buzurg represents a distinctive model of female sainthood grounded not in lineage or family status but in recognized spiritual authority and proximity to God.